COMPREHENSIVE APPROACHES TO THE TREATMENT AND REHABILITATION OF CHILDREN WITH GASTROINTESTINAL TRACT DYSFUNCTION - I.A. Belyaeva; G.V. Yatsyk; T.E. Borovik; V.A. Skvortsova ("Paediatrician" Publishers LLC, 2006)
In the article one of the actual problems of neonatology and children's gastroenterology - functional disorders of the gastrointestinal tract in newborn babies and infants is covered. The pathogenesis of digestive organs dysfunction, the classification and clinical characteristic of gastrointestinal disorders, the diagnostic possibilities and the correction of functional disorders of the gastrointestinal tract are presented. Key words: newborn babies, dysfunctions of the gastroin testinal tract, premature babies, diarrhea, regurgitation, constipation.